2016
DOI: 10.1111/1556-4029.13009
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term Geophysical Monitoring of Simulated Clandestine Graves using Electrical and Ground Penetrating Radar Methods: 4–6 Years After Burial

Abstract: This ongoing monitoring study provides forensic search teams with systematic geophysical data over simulated clandestine graves for comparison to active cases. Simulated “wrapped,” “naked,” and “control” burials were created. Multiple geophysical surveys were collected over 6 years, here showing data from 4 to 6 years after burial. Electrical resistivity (twin electrode and ERI), multifrequency GPR, grave and background soil water were collected. Resistivity surveys revealed that the naked burial had low‐resis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(19 citation statements)
references
References 52 publications
0
19
0
Order By: Relevance
“…These processes include gross postmortem changes (e.g., livor mortis, marbling, bloating), autolysis, putrefaction, insect larval development, scavenging activity, and many others. Taphonomy is relevant to medicolegal death investigation because proper interpretation of decomposition processes can accomplish investigative goals such as establishing the cause of death , locating clandestine graves , and estimating postmortem interval . An ecological approach to studying and applying taphonomy is often implemented because many decomposition processes are biologically mediated.…”
mentioning
confidence: 99%
“…These processes include gross postmortem changes (e.g., livor mortis, marbling, bloating), autolysis, putrefaction, insect larval development, scavenging activity, and many others. Taphonomy is relevant to medicolegal death investigation because proper interpretation of decomposition processes can accomplish investigative goals such as establishing the cause of death , locating clandestine graves , and estimating postmortem interval . An ecological approach to studying and applying taphonomy is often implemented because many decomposition processes are biologically mediated.…”
mentioning
confidence: 99%
“…These control studies have shown that the geophysical responses in active cases could be predicted, although responses seem to vary both temporally after burial and between different study sites. A few studies have also collected repeat (time-lapse) geophysical surveys over controlled experiments (e.g., [18,[47][48][49][50][51][52][53][54][55][56][57]), which have documented temporal changes in geophysical responses over their study periods.…”
mentioning
confidence: 99%
“…The local soil is a sandy loam with nearby borehole records (27) with a bedrock of Carboniferous (Westphalian) Butterton Sandstone bedrock present at ~2.5 m below ground level (bgl). This site has been previously used for forensic geophysical studies (27)(28)(29)47) but these are downslope of this investigation site so avoiding any soil contamination issues.…”
Section: Study Test Sitementioning
confidence: 99%
“…The use of pig cadavers as human analogues is well established in forensic science studies as they have similar chemical compositions, body sizes, tissue-to-body fat ratios, gut fauna, skin ⁄ hair types, and emissivity value to humans (27,28,(48)(49)(50). At the current research site their use has been approved by the Department for Environment, Food & Rural Affairs (DEFRA) and the School's Ethics Committees.…”
Section: Pig Cadavermentioning
confidence: 99%
See 1 more Smart Citation